2023
DOI: 10.1002/ehf2.14499
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance left ventricular filling pressure is linked to symptoms, signs and prognosis in heart failure

Ciaran Grafton‐Clarke,
Pankaj Garg,
Andrew J. Swift
et al.

Abstract: AimsLeft ventricular filling pressure (LVFP) can be estimated from cardiovascular magnetic resonance (CMR). We aimed to investigate whether CMR‐derived LVFP is associated with signs, symptoms, and prognosis in patients with recently diagnosed heart failure (HF).Methods and resultsThis study recruited 454 patients diagnosed with HF who underwent same‐day CMR and clinical assessment between February 2018 and January 2020. CMR‐derived LVFP was calculated, as previously, from long‐ and short‐axis cines. CMR‐derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Increased PAWP levels, whether invasively measured or non-invasively estimated, have repeatedly been linked to a worse prognosis in heart failure [ 38 , 39 ]. Studies have shown that an increase in PAWP is more closely associated with symptom burden and a worse prognosis than the elevation of LVEDP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased PAWP levels, whether invasively measured or non-invasively estimated, have repeatedly been linked to a worse prognosis in heart failure [ 38 , 39 ]. Studies have shown that an increase in PAWP is more closely associated with symptom burden and a worse prognosis than the elevation of LVEDP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 18 It is superior to transthoracic echocardiography in correctly classifying patients as having ‘normal’ or ‘raised’ filling pressures and can better determine the risk of cardiovascular death. Other large HF cohort studies have demonstrated the clinical significance of raised CMR-derived PCWP, 19 showing that elevated CMR-derived PCWP is strongly associated with symptoms (orthopnoea, breathlessness) and signs of HF (pleural effusions, lower limb oedema). Furthermore, raised CMR-derived PCWP is independently associated with subsequent HF hospitalization and major adverse cardiovascular events (MACEs).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, raised CMR-derived PCWP is independently associated with subsequent HF hospitalization and major adverse cardiovascular events (MACEs). 19 In addition to its role in HF, CMR-derived PCWP can also be used to measure acute and dynamic changes in preloading conditions on the LV during adenosine-administered first-pass perfusion CMR, where it has been observed to rise significantly. 20 …”
Section: Introductionmentioning
confidence: 99%